Extraction and isolation of alkaloids from the leaves of alseodaphne corneri (Lauraceae) (IR) - Jennie, Khoo Hui Chen (2015)
This phytochemical study is aimed to extract, isolate and identify alkaloids from Alseodaphne corneri leaves. The crude alkaloid was extracted by cold percolation followed by acid-base extraction until Mayer test showed negative result. Then, it was separated by conventional chromatographic methods using column chromatography and preparative thin layer chromatography. The structural elucidation of isolated alkaloids was then carried out by spectroscopic techniques; UV, IR, NMR and HRESIMS. The structures of the compounds were also determined by comparison with previous study. Isolation of alkaloids yielded one new benzylisoquinoline; (6,7- dimethoxyisoquinolinyl)-(2',5'-dihydroxy-4'-methoxyphenyl)-methanone 68, one bisbenylisoquinoline; obamegine 49, one oxoaporphines; atheroline 71, and five aporphine; isocorydine 48, N-methyllaurotetanine 51, laurotetanine 53, lirioferine 69 and norlirioferine 70. The benzylisoquinoline type alkaloid, lirioferine 69 and atheroline 71 were first reported in Alseodaphne genus while norlirioferine 70 was first isolated from Alseodaphne corneri species. These findings are very important as the elucidated alkaloids can be referred in future especially in identification of new alkaloid compound.